Jawaharlal Nehru rebel and statesman - Nanda, B. R. (Bal Ram) 1917- (New Delhi Oxford University Press, 1998)
Full of fascinating and rare halftones of Nehru, this biography strikes a much-needed balance between the adulation accorded Nehru during his lifetime and the denigration - often quite ill-founded - heaped upon since.
Originally published: 1995.
Keywords: Nehru, Jawaharlal -- 1889-1964.; Prime ministers -- India -- Biography; India -- History -- 1947-.